تسجيل نوع جديد من الأسماك المهاجرة إلى الشواطئ السورية في الحوض الشرقي للبحر الأبيض المتوسط، (السمكة البوقية Ruppell,1835 Fistularia commersonii,). (Latakia University Journal -Basic Sciences Series, 2018)
يأتي تسجيل نوع جديد من الأسماك المهاجرة إلى الشواطئ السورية للبحر الأبيض المتوسط، هذا العام 2002 م، ضمن إطار البرنامج الوطني للتنوع الحيوي في سورية، و الذي بدأ منذ حوالي العشرة سنوات ويؤكد استمرارية التغيرات البيئية في البحر الأبيض المتوسط(كارتفاع درجة الملوحة حتى 4% ، و درجة الحرارة التي تبلغ صيفاً أكثر من28 ْم). هذا وقد كشف الحصر الأخير للأسماك البحرية السورية الذي جرى في التسعينات عن تسعة أنواع مهاجرة من البحر الأحمر، و أحد عشر نوعاً من غربي البحر المتوسط. وفي هذه الدراسة الحقلية ، تم تسجيل نوع سمكي مهاجر،هو السمكة البوقية Fistularia commersonii والتي ظهرت سابقاً في شباك الجرف في المياه الساحلية لمدينتي طرطوس واللاذقيةوسجلت علمياً خلال هذا العام 2002 م لأول مرة. درست بعض الخصائص المورفولوجية والقياسية لهذه السمكة. وحفظت في مخابرقسم علم الحياة والمعهد العالي للبحوث البحرية بجامعة تشرين. This year 2002,the recording of new species from migrant fish to Syrian shore of Mediterranean sea comes in the frame of the National program of the Biological Diversity in Syria, which began about ten years ago. This emphasizes the continuous ecological exchanges in the Mediterranean Sea such as increasing salinity up to 4%, temperature that may reach 28ْ in summer. The recent study on Syrian marine fish made in nineties has shown migrating species from the Red Sea and 11 species from the western Mediterranean. In this laboratorial and field studies, migrant fish species were recorded, that is the Cornetfish, which was caught for the first time in Trawl nets at coast water of Lattakia and Tartus cities, during 2002. Some Morphometric characteristics had been studied for this fish, and preserved in Biology Dept and High Institute of Marine Research Laboratories of Tishreen University.